Influence of wave climate on architecture and landscape characteristics of Posidonia oceanica meadows. (3rd November 2016) - Pace, Matthew; Borg, Joseph A.; Galdies, Charles; Malhotra, Amit
Abstract: Seagrass meadow characteristics, including distribution, shape, size and within‐meadow architectural features, may be influenced by various physical factors, including hydrodynamic forces. However, such influences have hardly been assessed for meadows of the ecologically important and endemic Mediterranean seagrass Posidonia oceanica . The distribution of P. oceanica meadows at five sites in the Maltese Islands was mapped to a depth of c . 15 m using a combination of aerial photography and SCUBA diving surveys. Estimates of wind‐generated wave energy and energy attenuated by depth were computed using the hydrodynamic model WEMo (Wave Exposure Model). Metrics for P. oceanica landscape features were calculated using FRAGSTATS for replicate 2500 m 2 subsamples taken from the seagrass habitat maps in order to explore the influence of wave dynamics at the landscape scale. Data on within‐meadow architectural attributes were collected from five sites and analysed for relationships with wave energy. The results indicate that landscape and architectural features of P. oceanica meadows located within the 6–11 m depth range are significantly influenced by wave climate. Posidonia oceanica meadows tend to be patchier and have low overall cover, more complex patch shapes and reduced within‐patch architectural complexity along a wave exposure gradient from low to high energy. The findings from the present study provide new insight into the influence of hydrodynamic factors on the natural dynamism of P. oceanica meadow landscape and architecture, which has implications for the conservation and management of the habitat.